2012
DOI: 10.1007/s10530-012-0390-y
|View full text |Cite
|
Sign up to set email alerts
|

Global warming may freeze the invasion of big-headed ants

Abstract: Climate change and invasive species are two of the most serious threats of biodiversity. A general concern is that these threats interact, and that a globally warming climate could favour invasive species. In this study we investigate the invasive potential of one of the ''100 of the world's worst invasive species'', the big-headed ant Pheidole megacephala. Using ecological niche models, we estimated the species' potential suitable habitat in 2020, 2050 and 2080. With an ensemble forecast obtained from five di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 69 publications
1
19
0
Order By: Relevance
“…The selected variables were (in the order of their relative contribution to the Maxent model): Precipitation of the driest month, isothermality, precipitation of the warmest quarter and maximum temperature of the warmest month. These variables are believed to directly influence ant distributions because many features of ant biology are sensitive to small differences in temperature [16] or humidity, for example foraging [11], oviposition rates [44], survival [10], the structure of foraging networks [12].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The selected variables were (in the order of their relative contribution to the Maxent model): Precipitation of the driest month, isothermality, precipitation of the warmest quarter and maximum temperature of the warmest month. These variables are believed to directly influence ant distributions because many features of ant biology are sensitive to small differences in temperature [16] or humidity, for example foraging [11], oviposition rates [44], survival [10], the structure of foraging networks [12].…”
Section: Methodsmentioning
confidence: 99%
“…Finally we used the Maximum Entropy Method (Maxent) which estimates a probability distribution of a species being present by seeking the most widespread distribution, given a set of constraints [18], [57], [58]. For a more detailed description of these algorithms see [16], [19]. All models were run using the ModEco Platform with default parameters [59].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout the 20th century, shifts in the latitudinal (see example in Parmesan and Yohe 2003) and altitudinal (Lenoir et al 2008) ranges of different plant species have been observed and related to rising temperatures. Previous work suggests that the distribution of invasive species will likely increase due to climate and land-use changes (Pyšek et al 2002;Kleinbauer et al 2010;Vicente et al 2010Vicente et al , 2011Vicente et al , 2013, but this is not always the case (Parker-Allie et al 2009;Bertelsmeier et al 2013;Gallagher et al 2013). However, these results were associated with individual species and/or were locally dependent, and general conclusions are difficult to achieve (see Bellard et al 2013).…”
Section: Introductionmentioning
confidence: 99%